2018
DOI: 10.1161/circulationaha.118.032410
|View full text |Cite
|
Sign up to set email alerts
|

Higher Aortic Stiffness Is Related to Lower Cerebral Blood Flow and Preserved Cerebrovascular Reactivity in Older Adults

Abstract: Greater aortic stiffening relates to lower regional CBF and higher CVR in cognitively normal older adults, especially among individuals with increased genetic predisposition for Alzheimer's disease. Central arterial stiffening may contribute to reductions in regional CBF despite preserved cerebrovascular reserve capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 49 publications
9
110
4
3
Order By: Relevance
“…Increased arterial stiffness affects the hemodynamic function of the cerebral vasculature. For example, a recent study found an association between aortic stiffening and reduced rCBF in cognitively normal older adults, without clinical presentation of stroke and dementia [67]. Interestingly, the study also demonstrated that APOE-ε4 carriers were found to have higher pulse wave velocity and lower rCBF in the whole brain and in the temporal lobe, compared to non APOE-ε4 carriers.…”
Section: Klohsmentioning
confidence: 78%
“…Increased arterial stiffness affects the hemodynamic function of the cerebral vasculature. For example, a recent study found an association between aortic stiffening and reduced rCBF in cognitively normal older adults, without clinical presentation of stroke and dementia [67]. Interestingly, the study also demonstrated that APOE-ε4 carriers were found to have higher pulse wave velocity and lower rCBF in the whole brain and in the temporal lobe, compared to non APOE-ε4 carriers.…”
Section: Klohsmentioning
confidence: 78%
“…The same is true for functional connectivity measured in resting‐state data (Brier et al, ). Increased carotid PWV in aging has been associated with reduced blood flow in aging (Fisher et al, ; Jefferson et al, ; Kroner et al, ) as well as higher blood pressure (Sawabe et al, ). Arterial stiffening has also been associated with reduced CVR (Flück et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Correlational studies in human subjects find that large elastic artery stiffness is associated with resistance artery dysfunction (Mitchell et al, 2005), lower cerebral blood flow (Jefferson et al, 2018;Tarumi, Shah, Tanaka, & Haley, 2011), cognitive impairment (Hanon et al, 2005;Meyer et al, 2017;Mitchell et al, 2011;Pase et al, 2016) and…”
Section: Introductionmentioning
confidence: 99%